The Assessment of Mangrove Community Based on Vegetation Structure at Cendi Manik, Sekotong District, West Lombok, West Nusa Tenggara - Baiq Farista; Arben Virgota (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
The area at the research site has a mangrove community that is experiencing disturbances due to the conversion of land into ponds. Therefore, the purpose of this study was to assess the actual condition of mangrove vegetation after land conversion. The method used in this research is a survey and the sampling point is determined randomly (random sampling). Furthermore, observations were made on two existing mangrove blocks, namely the Natural Block and the Rehabilitation Block. Observation plots were placed randomly in the Natural Bok and Rehabilitation Block. Randomization was carried out on the regional map by making a grid measuring 10x10m and numbered. The data were analyzed using the analysis of the diversity index value (Shannon-Wiener), the evenness index (Evenness), the proportion of vegetation at each growth level and the pattern of vegetation distribution (Morisita Index). The results showed that the value of species diversity in the Natural Block was 0.95 and the Rehabilitation Block was 0.99. This value is included in the category of low diversity. The evenness index obtained a value of 0.49 in the Natural Block and 0.45 in the Rehabilitation Block. This value indicates that the distribution of the number of individuals in each species is not evenly distributed. Vegetation is dominated by Trees (in the Natural Block) and Saplings (in the Rehabilitation block). The vegetation in the Natural Block is older than the Rehabilitation Block. Meanwhile, based on the value of the Morisita index, the distribution pattern of mangrove vegetation in the study area is included in the cluster category.